The Theory of Share Tenancy Revisited - Hsiao, J. C. (Journal of Political Economy, 1975)
The argument of efficient versus inefficient allocation of resources under share tenancy has received considerable attention in the literature. The purpose of this article is to show that share leasing does not result in inefficient resource use. This paper demonstrates that an arrangement in which rent is some percentage of farm output during a certain period of time for a given acreage yields an equilibrium solution with an efficient allocation of resources. A geometric proof, economic interpretation, and some general observations are provided.